Free volume modifications in chalcone chromophore doped PMMA films by electron irradiation: Positron annihilation study. (March 2018) - Ismayil,; Ravindrachary, V.; Praveena, S.D.; Mahesha, M.G.
Abstract: The free volume related fluorescence behaviour in electron beam irradiated chalcone chromophore doped Poly(methyl methacrylate) (PMMA) composite films have been studied using FTIR, UV–Visible, XRD and Positron Annihilation techniques. From the FTIR spectral study it is found that the formation of polarons and bipolaron takes place due to cross linking as well as chain scission processes at lower and higher doses respectively. It reveals that the formation of various polaronic defect levels upon irradiation is responsible for the creation of three optical energy band gaps within the polymer films as obtained from UV–Visible spectra. The crosslinking process at lower doses increases the distance between the pendant groups to reduce the interchain distance and chain scission process at higher doses decreases interchain separation to enhance the number of polarons in the polymer composites as suggested by XRD studies. The fluorescence studies show the enhancement of fluorescence emission at lower doses and reduction at higher doses under electron irradiation. The positron annihilation study suggests that the low radiation doses induce crosslinking which affect the free volume properties and in turn hinders the chalcone molecular rotation within the polymer composite. At higher doses chain scission process support polymer matrix relaxation and facilitates non-radiative transition of the chromophore upon excitation. This study shows that fluorescence enhancement and mobility of chromophore within the polymer matrix is directly related to the free volume around it. Highlights: Microstructural modifications in electron irradiated PMMA/MPDMAPP are reported. Formation of polarons takes place due to cross linking process at lower doses. Bipolaron formation occurs via chain scission process at higher doses. Free volume related parameters are studied using PALS technique. Fluorescence enhancement is directly related to free volume around polymer matrix.